Circular information flows in industrialized housing construction: the case of a multi-family housing product platform in Sweden - Kedir, Firehiwot; Hall, Daniel M.; Brantvall, Sara; Lessing, Jerker; Hollberg, Alexander; Soman, Ranjith K. (Construction innovation, 2024)
Purpose This paper aims to conduct a qualitative assessment of synergies between information flows of a multifamily product platform used for industrialized housing and materials passports that can promote a circular economy in the construction industry. Design/methodology/approach Using a single case study method, the research assesses the availability and accessibility of materials passport-relevant information generated by a leading Swedish industrialized housing construction firm. Data is collected using semistructured interviews, document analysis and an extended research visit. Findings The research findings identify the functional layers of the product platform, map the information flow using a process diagram, assess the availability and accessibility of material passport relevant information by lifecycle stage and actor, and summarize the key points using a SWOT (strengths, weaknesses, opportunities and threats) analysis. Research limitations/implications The three main implications are: the technical and process platforms used in industrialized construction allow for generating standardized, digital and reusable information; the vertical integration of trades and long-term relationships with suppliers improve transparency and reduce fragmentation in information flows; and the design-build-operate business model strategy incentivizes actors to manage information flows in the use phase. Practical implications Industrialized construction firms can use this paper as an approach to understand and map their information flows to identify suitable approaches to generate and manage materials passports. Originality/value The specific characteristics of product platforms and industrialized construction provide a unique opportunity for circular information flow across the building lifecycle, which can support material passport adoption to a degree not often found in the traditional construction industry.